Peningkatan Hasil Belajar Tematik Melalui Penerapan Model Problem Based Learning dengan Media Mind Mapping - Rizki Harlinda Putri; Nyoto Hardjono (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
This type of research is Classroom Action Research using the design of the Kemmis and Mc Taggart models. This study aims to describe the steps of problem based learning model that is able to increase thematic learning outcomes the student in one of elementary schools in Salatiga. The action is carried out in 2 cycles consisting of 3 meetings each cycle. Data collection was carried out with test and non-test techniques. The subjects of this reseach were the third grade students of SD Negeri Sidorejo Lor 01 Salatiga 2nd semester academuc year of 2017/2018 with the 39 students.based on the results of data analysis and observations, learning outcomes in pre cycle without using problem based learning model 59%, while in cycles 1 and 2 using the problem based learning model were 74.4 % and 92.3 % respectively. Based on these data it can be concluded that there is an increase in learning models.